The Uniqueness of Megapodius reinwardt and the Wisdom of the Local Community as Tourism Attraction and Conservation at Moyo Island - Yamin, M.; Khairuddin, Khairuddin; Jamaluddin, Jamaluddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The distribution, graduation and conservation of Megapodius reinwardt based on the ecological knowledge of local residents to support ecotourism on moyo island, has been carried out. The objectives are: 1) to obtain an accurate picture of the distribution of the population and its behavior, 2) knowledge of the ecology of the local population, 3) perception and behavior of the local population, 4) to increase the population, and 5) to carry out conservation to prevent its extinction in the Moyo Island. This research consists of two stages of activities, namely first, mapping population distribution, nest analysis, diseases, pathogens, interviews and discussions with local community about their perception and knowledge about M. reinwardt, document study about tourist visits; second, building awareness and participation of local community to support M. reinwardt conservation activities, formulating its conservation design and identifying potential nests as tourist attractions. The perception of the local residents of Moyo Island towards the existence of M. reinwardt is useful in supporting the fulfillment of their life needs directly or indirectly. Locals believe that by keeping M. reinwardt, his life needs can be met. In addition, the locals of Moyo Island think that laboring the bird at the time of laying eggs will be